Transgene-Free Editing of PPO2 in Elite Potato Cultivar YAGANA for Reduced Postharvest Browning - Zuniga-Navarro, G (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Enzymatic browning, driven by polyphenol oxidase (PPO), remains a major postharvest challenge for potato (Solanum tuberosum L.), reducing product quality, shelf life, and consumer acceptance. To mitigate this trait in the elite tetraploid cultivar Yagana-INIA , we applied a geminivirus-derived CRISPR-Cas9 system to edit the StPPO genes most highly expressed in tubers, StPPO1 and particularly StPPO2. A paired-gRNA strategy generated a double-cut deletion in StPPO1, while StPPO2 editing required a complementary single-gRNA screening workflow. High-resolution fragment analysis and sequencing identified three StPPO2-edited lines, including one that lacked GFP, Cas9, and Rep/RepA sequences, confirming a transgene-free editing outcome. Edited tubers exhibited visibly reduced browning relative to wild type, and biochemical assays showed decreased PPO activity consistent with targeted disruption of StPPO2. Amplicon sequencing verified monoallelic editing at the gRNA2 site in the non-transgenic line. These results demonstrate the utility of a replicon-based CRISPR system for achieving targeted, transgene-free edits in tetraploid potato and identify a non-GM StPPO2-edited line with improved postharvest quality under Chile s regulatory framework.
Keywords: CRISPR/Cas9; geminivirus-derived replicon; polyphenol oxidase; postharvest browning; regulatory compliance; Solanum tuberosum; StPPO2; tetraploid potato; transgene-free genome editing